The One Editorial of "SehMahi Al-Zubair"....... Represents Thousand Years History of "Travelogue" - Ahmad, Muhammad; Hussain, Shazra (sourcecoder, 2023)
Urdu Academy Bahawalpur established in 1959, started its research journal named "SehMahi Al-Zubair" in 1961. The first editor was Allama Syed GhulmShabbirBukhari who worked for very shot time (1959 to April 1961). After him Syed Masood Hassan ShahabDehelvi joined the Academy as it's second editor. Urdu Academy pubished first special number i-e "GhairMulkiAfsana Number" in 1961 and published second one in 1962 i-e "Safarnama Number". From the first day, Editor wrote the Editorials in each and every Magzine of "Al-Zubair". He wrote the historical editorials for special Magzines like in "Safarnama Number" in 1962. Editorial of "Safarnama Number" has an astonishing history of almost 1000 years of "Travelogue" as well as more than 100 years history of "Urdu Travelogue". The editor wrote that the actual starting of travelling is the Hijrat of Hazrat Muhammad P.B.U.H from Makkah to Madinah. He proved it by Muhaddiseen's opinion. The editor also told that writing of "Travelogue" was started by the Muslims in 4th century of Hijri calendar. Therefore this Editorial is very important for the students of Urdu Language & Literature and as well as History. This article is based upon said editorial which is not only the editorial but also the document comprising the history of 1000 years of Travelogue Writing.